PENGARUH REVALUASI ASET TERHADAP NILAI PERUSAHAAN - Andini Marselina (2017)
his study was conducted to examine the effect of variable Asset Revaluation on Firm Value at the Company's manufacturing listed in Indonesia Stock Exchange during the years 2012 to 2015. Independent variabels used in this research were asset revaluation. Dependent variabels used in this research is firm value. The population in this study is companies manufacturing contained in the Indonesia Stock Exchange during 2012 to 2015. Sample were obtained in this study of 50 samples selected by purposive sampling method. After outlier data using boxplot method for influence of revaluation toward stockprice and boxplot method for influence of asset revaluation toward stock return, which eventually resulted 35 samples for influence of revaluation toward stockprice and 39 samples for influence of revaluation toward return stock to be analyzed and tested. Data were tested using multiple linear regression method with a significance level 5%. The results of the testing showed that: (1) Asset revaluation has no significant influence on the stockprice with a significance level of 0.900 is greater than the specified level α = 0.05. (2) Asset revaluation has no significant effect on the return stock because it has a significance level of 0.466 is greater than the specified level α = 0.05.